Starostinia, a new generic replacement name for Ironella Starostina & Krasnov, 1970 (Anthozoa: Scleractinia: Rhipidogyridae) non Cobb, 1920 (Nematoda: Ironidae) - Doweld, Alexander B. (Zootaxa, 2014)
The fossil genus Ironella Starostina & Krasnov (type species I. giseldonensis by original designation) was established (in Krasnov & Starostina 1970: 79) for distinctive scleractinian corals from Northern Caucasus of Russia (Northern Ossetia). However, Ironella Cobb (1920: 277), a living nematode (Adenophorea: Enoplida: Ironidae), preceded the fossil coral name, which becomes a preoccupied later homonym. The nematod Ironella is well recognized in modern zoology (Nematoda—LSID urn:lsid:marinespecies.org:taxname:227324), and in this connection a new generic designation is necessary for the later homonymic fossil scleractinian genus.